Boron-containing MFI-type zeolites with a hierarchical nanosheet assembly for lipase immobilization. Issue 13 (10th March 2017) - Marthala, V. R. Reddy; Urmoneit, Lynn; Zhou, Zhou; Machoke, Albert G. F.; Schmiele, Martin; Unruh, Tobias; Schwieger, Wilhelm; Hartmann, Martin
Abstract : Ball-like nanosheet assemblies of boron-containing MFI-type zeolites were synthesized using bifunctional surfactant molecules. The pore size of ca . 6.5 nm allows encapsulation of the enzyme lipase. Abstract : Hierarchical nanosheet assemblies of boron-containing MFI-type zeolites were successfully synthesized using bifunctional surfactant molecules under static conditions. With the optimized Si/B = 50 in the synthesis gel, a material with high specific surface area (483 m 2 g −1 ) and a maximum pore size of 6.5 nm suitable for lipase encapsulation was obtained.